Long-term safety and tolerability of erenumab: Three-plus year results from a five-year open-label extension study in episodic migraine. (October 2019) - Ashina, Messoud; Goadsby, Peter J; Reuter, Uwe; Silberstein, Stephen; Dodick, David; Rippon, Gregory A; Klatt, Jan; Xue, Fei; Chia, Victoria; Zhang, Feng; Cheng, Sunfa; Mikol, Daniel D
Background: Previously published three-month placebo-controlled and one-year open-label clinical trial data have provided information on the efficacy and safety of erenumab. Methods: Interim analysis was undertaken from an ongoing five-year open-label treatment phase after all patients completed three years in the open-label treatment phase or discontinued the study. Adult patients with episodic migraine enrolled in the open-label treatment phase initially received 70 mg erenumab monthly. A protocol amendment increased the dosage to 140 mg monthly to assess long-term safety of the higher dose. Safety and tolerability were assessed by monitoring adverse events, electrocardiograms, laboratory assessments, and vital signs. Results: Of 383 patients enrolled in the open-label treatment phase, at data cutoff 235 (61.3%) remained in the study, all received 140 mg for ≥1 year. Median (Q1, Q3) exposure (70 or 140 mg) for all patients enrolled was 3.2 (1.3, 3.4) years. The most frequent adverse events (≥4.0/100 patient-years) were reported as viral upper respiratory tract infection, sinusitis, influenza, and back pain. Exposure-adjusted serious adverse event rates were 4.2/100 patient-years. There was no increase in cardiovascular events over time. Conclusions: In this long-term study of a CGRP-receptor antibody, erenumab was found to be safe and well-tolerated with a spectrum and rate of adverse events consistent with shorter-term placebo-controlled studies. Trial registration: ClinicalTrials.gov NCT01952574